Field Evaluation of Trichogramma chilonis (Ishii) for the Management of Shoot Borers in Sugarcane - Visalakshi, M.; Bhavani, B.; Rao, S. Govinda (International Journal of Bio-resource and Stress Management, 2023)
Demonstrations were conducted to evaluate the efficacy of Trichogramma chilonis for the management of shoot borers in sugarcane in three villages of Visakhapatnam district, Andhra Pradesh during 2012–13. Field release of Trichogramma chilonis @ 50,000 ha-1 release-1 from 30 days after planting, four times at 7–10 day interval and two times after node formation reduced the early shoot borer by 89.67% and internode borer by 18.82% in biocontrol plots in comparison to farmers’ plots. Adoption of integrated pest management practices viz., trash mulching @ 3 t ha-1 at planting and release of T. chilonis @ 50,000 ha-1 from 30 days after planting, four releases at 7−10 day interval and two releases after node formation effective in reducing early shoot borer by 78.31% and internode borer by 88.38% in IPM plots in comparison to farmers plots. The results showed that utilization of T. chilonis against shoot borers in biocontrol plot produced high cane yield of 92.82 t ha-1 with a benefit cost ratio of 2.21:1 compared to farmers plot (78.48 t ha-1 with a B:C ratio of 1.82). Similarly, IPM plots recorded high cane yield i.e., 68.2 t ha-1 and higher B:C ratio of 1.79, compared to farmers plot (57.04 t ha-1 with B:C ratio of 1.15). Use of biocontrol agent in plant protection is a low cost technology with reduction in cost of plant protection to an extent of 79% in biocontrol plot and 41.2% in IPM plot with enhanced cane yields of 14.43 t ha-1 and 11.16 t ha-1 respectively.